(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Avipox is a viral disease of fowl and pigeon which is characterized by proliferative and nodular lesions in the feather-free parts of the skin or fibro-necrotic and proliferating part in the mouth, esophagus, and mucous membrane of the upper respiratory tract. This investigation was carried out with an aim to isolate and molecular detection of Fowl pox virus (FPV) and Pigeon pox virus (PPV) for development of live attenuated vaccine seeds from the local virus isolates. In this study, nodular lesions were collected from seven pigeons and four chickens from different areas of Mymensingh in Bangladesh which were affected by pox. Viral inoculums were prepared and DNA materials were extracted for PCR-based identification of P4b genes. Detection of virus was confirmed by PCR following propagation into 9-11 days old embryonated chicken egg (ECE) and also chicken embryo fibroblast (CEF) cell culture All the field samples were found positive for FPV and PPV by PCRR. These field isolates were propagated and attenuated in duck embryo through CAM route and duck embryo fibroblast (DEF) cell culture for the development of live attenuated vaccine seeds. Attenuation of both FPV and PPV were successful in duck embryo through CAM route and duck embryo fibroblast (DEF) cell culture after serial six passages. Attenuation of the virus was confirmed by inoculation into experimental birds. Inoculation of attenuated FPV and PPV in chicken and pigeon respectively exhibited no pox lesions whereas control chicken and pigeon inoculated with field isolates develop nodular lesions. Both FPV and PPV were confirmed from both groups of birds by PCR. These attenuated local isolates of FPV and PPV could be used as potential vaccine candidates for the prevention and control of fowl pox and pigeon pox in Bangladesh. J. Bangladesh Agril. Univ. 17(2): 211–219, June 2019